레바미피드의 용해도가 향상된 사원 고체분산체 시스템 - 조대영(Dae Yeong Cho); 김문정(Moon Jung Kim); 김경수(Kyeong Soo Kim) (Yaghag-hoi-ji, 2024)
The objective of this study was to prepare and evaluate microcapsules based on quaternary solid dispersions containing rebamipide to enhance solubility and dissolution rates. After screening numerous pH modifiers, polymers, and surfactants, L-arginine, gelatin, and SLS were selected as the alkalizer, soluble polymer, and surfactant, respectively. Various microcapsules were prepared through a spray-drying process, and their physicochemical properties, solubility, and dissolution profiles were investigated. The microcapsules containing rebamipide, L-arginine, gelatin, and SLS in a weight ratio of 1:1:0.5:1 provided an amorphous drug form and a spherical particle shape. They exhibited excellent solubility and dissolution rates compared to pure rebamipide powder. Additionally, the microcapsules were evaluated against commercial tablets and showed superior dissolution rates in both water and a pH 4.0 buffer compared to the rebamipide powder and the tablets. Furthermore, they enhanced stability by reducing the recrystallization rate of rebamipide, which tends to recrystallize quickly at low pH. Consequently, we successfully prepared microcapsules based on quaternary solid dispersions of rebamipide to enhance solubility and dissolution rates. These microcapsules could be utilized in formulation development studies to improve the bioavailability of poorly soluble rebamipide. KCI Citation Count: 0